Thioredoxin from Escherichia coli as a role model of molecular recognition, folding, dynamics and function - Vazquez, Diego Sebastian (2015)
Thioredoxin (TRX) catalyzes redox reactions via the reversible oxidation of the conserved active center CGPC and it is involved in multiple biological processes, some of them linked to redox activity while others not. TRX is a globular, thermodynamically stable and monomeric alpha/beta protein with a structure characterized by a central beta-sheet surrounded by alpha-helices. In this review we discuss central aspects of folding, dynamics and function of Escherichia coli TRX (EcTRX), pointing to the characterization of the full-length protein and of relevant fragments. In addition, we focus on the critical role that the C-terminal alpha-helical element plays in a late event in the consolidation of the overall EcTRX fold. Furthermore, we address the characterization of internal molecular motions by NMR and molecular dynamics simulation techniques. Finally, we review important aspects of the relationship among structure, dynamics and enzymatic function of this key redox protein.